The bacteriostatic spectrum and inhibitory mechanism of glycocin F, a bacteriocin from Lactobacillus plantarum KW30 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University, Palmerston North, New Zealand - Kerr, Andrew Philip (Massey University, 2013)
Bacteriocins have been deemed the “microbial weapon of choice”. The ability to ribosomally synthesise these toxins means that their peptide scaffolds can be rapidly adapted to optimise stability, potency and specificity, allowing producers to outgrow closely related strains and become dominant. In some cases, a bacteriocin may inhibit a broader spectrum of microbes than just its species/genus of origin. Recently, the bacteriocin glycocin F (GccF), produced byLactobacillus plantarum KW30, was biochemically and structurally characterised. GccF isunique, as it has two covalently linked N-acetylglucosamine (GlcNAc) moieties, one O-linkedand one S-linked, that are critical for the inhibition of target cell growth. How GccF causes bacteriostasis in sensitive Lactobacillus cells was unknown. Experiments were developed and conducted to probe the antimicrobial spectrum of GccF and how thisspectrum is affected by free GlcNAc. It was found that a variety of species and strains, not just those closely related to L. plantarum KW30, were inhibited by the addition of GccF to cultures in solid or liquid media. Susceptible strains were identified in the genera Streptococcus, Enterococcus, and Bacillus. Interestingly, assays indicated that free GlcNAc plays a more dynamic role in modulating GccF activity than previously thought. The protective effect of high concentrations of GlcNAc, including the reversal of GccF-induced bacteriostasis, was confirmed for susceptible L. plantarum strains, but surprisingly addition ofrelatively low concentrations of GlcNAc prior to GccF led to a concentration-dependent increase in bacteriostasis for some other species including Enterococcus faecalis. GccF’s mechanism of action was found to be different to the bactericidal membrane-permeabilising effect of the lantibiotic nisin, as L. plantarum cells treated with GccF did not die, and there was no substantial release of ATP from cells upon GccF-induced bacteriostasis. It was also found that for Gram-negative bacteria, which are generally resistant to GccF, growth inhibition was greatly enhanced if the integrity of the outer membrane was compromised by treatment with polymyxin, or by expression of a ‘leaky’ mutant of the outer membrane secretin PulD. Thus GccF-mediated inhibition of growth is limited to Gram-positive bacteria mainly because of the barrier function of the Gram-negative outer membrane. Experiments to identify changes in E. faecalis V583 gene expression or the levels of specific proteins in response to free GlcNAc were inconclusive due to time constraints. Further research is needed to determine GccF’s exact mechanism of action. The results of experiments with GccF, with and without added GlcNAc, on a range of bacterialspecies led to a hypothetical model for the mechanism of action of GccF, specifically that GccF may be ‘hijacking’ GlcNAc-specific phosphotransferase system signalling pathways.This could disrupt normal GlcNAc metabolism, perhaps resulting in UDP-GlcNAc becominglimiting for peptidoglycan synthesis, thus preventing cell wall expansion, and normal cellgrowth and division.
Keywords: Bacteriocins; Glycocin F; Lactobacillus plantarum